واقع المشهد اللغوي في فلسطين ومحاولات التهويد والعبرنة - Elsayed Mohamed Salem, Salem Elawadi (2018)
This research deals with the linguistic conflict between the Arabic language and the Hebrew language in occupied Palestine, and the worrying state of Arabic. Although Arabic is a second official language under the law, Israel is working to remove it from various areas of life and to replace it in Hebrew One of the pillars of the Zionist project to ensure the survival of their state is alleged through the soft padded Judaization. This study is to highlight the need to preserve the Arabic language as part of the preservation of the Palestinian presence, to learn the linguistic history of the Hebrew language, to clarify the linguistic scene in Palestine, and the location of the Arabic language between the fierce Zionist attacks and an attempt to transcribe it as part of the plans of the Zionist entity to eliminate the existence Palestinian conflict. The aim of this research is to: 1. To alert the importance of the Arabic language in preserving the Arab identity and the historical memory and the Palestinian narrative. 2. The location of both Arabic and Hebrew in the old Palestinian history. 3. Clarifying the relationship between the establishment of the Zionist entity and the revival of the Hebrew language. 4. Attempt to Judaize the language of the Palestinian inside. The research followed the historical approach, which was used in the first topic; to mention historical profiles of the land of Palestine, the history of the Jews and their Hebrew language, and the descriptive approach to collecting, describing and interpreting the basic scientific material.